2018
DOI: 10.7150/ijms.27318
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human Umbilical Vein Endothelial Cells in Osteogenic Differentiation of Dental Follicle-Derived Stem Cells in In Vitro Co-cultures

Abstract: Angiogenesis and vascularization are essential for the growth and survival of most tissues. Engineered bone tissue requires an active blood vessel network for survival and integration with mature host tissue. Angiogenesis also has an effect on cell growth and differentiation in vitro. However, the effect of angiogenic factors on osteoprogenitor cell differentiation remains unclear. We studied the effects of human umbilical vein endothelial cells (HUVECs) on osteogenic differentiation of dental follicle-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…This study also suggested that a HUVECs:MSCs co-culture ratio of 1:1 is the best combination to obtain both osteogenic and angiogenic differentiation. These results are consistent with that obtained in the other studies, where 1:1 ratio provided robust and stable vascular networks while enabling bone-like tissue formation [15,117].…”
Section: Co-culturing Systems and Optimization Of Conditionssupporting
confidence: 93%
“…This study also suggested that a HUVECs:MSCs co-culture ratio of 1:1 is the best combination to obtain both osteogenic and angiogenic differentiation. These results are consistent with that obtained in the other studies, where 1:1 ratio provided robust and stable vascular networks while enabling bone-like tissue formation [15,117].…”
Section: Co-culturing Systems and Optimization Of Conditionssupporting
confidence: 93%
“…Given their remarkable properties, DFCs have been considered pivotal seed cells in periodontal tissue engineering and hopefully provide a novel approach to regeneration therapy. 7,28 Previous studies have emphasized the accurate transfer of genetic information, which is essential for life. RNA Pol II can accelerate translation by the enzymatic machinery to transcribe protein-coding genes into mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no significant difference of osteogenic differentiation seen between predifferentiated MSC co-culture group and nonpredifferentiated MSC (data not shown). Therefore, it was deduced that osteogenic differentiation of MSCs before co-culture does not have any effect on their metabolic activity, which has been reported earlier [63,64]. This shows that osteogenic preinduction of MSCs before co-culture did not help in increase of osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 52%